THE ABRASIVE WEAR BEHAVIOR ANALYSIS OF THE ACRYLIC RESINS ARTIFICIAL TEETH - Elena Raluca Baciu; Roxana Ionela Vasluianu; Nicoleta Ioanid; Alice Murariu; Daniel Pavăl; Cătălina Cioloca Holban; Cosmin Ionuț Crețu; Dana Gabriela Budală (Romanian Society of Oral Rehabilitation, 2021)
The mechanical properties of artificial teeth play an important role in the long-term functionality of removable partial prosthesis or complete dentures. Aim: To highlight the behavior of acrylic teeth according to the speed of mass wear rate. Materials and method: There were used the upper central incisors made industrially from methyl polymethacrylate from different manufacturers. The mass loss was calculated using an analytical balance, before and after each determination. Results: The use of 20 N and 30 N forces for acrylic teeth corresponding to commercial Acry Rock and Eray Deluxe products has similar values. Low values resulted in the case of commercial products Acry Plus (F = 20 N) and Quint Plus (F = 30 N). Conclusions: In addition to the composition of acrylic teeth, layering plays a key role in providing wear resistance.